The Portrayal of Hegemony and Patriarchy in Louise O’ Neill’s Only Ever Yours - Nurin Naufina (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2021)
This study analyzes patriarchal hegemony portrayed in a dystopian world where young girls are hegemonized to fulfill patriarchal interests written by Louise O’ Neill, Only Ever Yours. As a counter to utopian writing, dystopian literature emerged as a subgenre of speculative fiction. The objectives of this study are to elucidate the kinds of patriarchal structures and media operated in portraying patriarchal hegemony in the novel. This study employs Antonio Gramsci’s hegemony theory along with the concept of patriarchy by Sylvia Walby. This study is literary criticism as the researcher interprets and analyzes the literary work. It employs a sociological approach for the analysis and Sylvia Walby’s six structures of patriarchy theory along with Gramsci’s theory. The data are taken from the words, phrases, and sentences in Only Ever Yours published in 2015. The researcher took the data by identifying, classifying and analyzing the data by elucidating the data with the theories. The result of this study shows that there are three patriarchal structures portrayed in the novel which are patriarchal mode of production, patriarchal state, and patriarchal culture. On the other hand, patriarchal hegemony is portrayed through the medium of television.